Working technology with psychosomatic symptoms and conversion disorder in psychotherapy and counseling - Vaskivska Світлана (Psychosomatic Medicine and General Practice, 2021)
Background. Overcoming accusations of unproven soul-body connection can be demonstrated by a streamlined system of unloading the psychological layers behind the physical symptom. Purpose of the article. To structure in detail and algorithmize psychological work with psychosomatic symptoms and conversion disorder, and to present it in the form of a well-thought-out and proven technological process Results. The subject of technological influence in psychotherapeutic work with a conversion symptom is the body - as an area of the unconscious, represented by a dream process (A. Mindel "Dreaming body"). The hidden "logic" of conversion can be established by working with three systems of representative experience - proprioceptive, iconic, and symbolic (J. Sandler, J. Bastiaans, G. Murphy). In Technological means of work with the psychosomatic symptom, such working technologies are 1) Tracking illness technologies; 2) Technologies for finding the trigger of psychosomatic disorder; 3) Technologies for the formation of conditions for access to processes in the body; 4) Technologies of conscious communication with the body; 5) Processing technologies; 6) Technologies of transition to the symbolic level of reading and elaboration of representatives of experience. The tools for working with the physical, emotional, and symbolic-figurative components of the experience of psychosomatic disorders are offered. A standardized algorithm of psychological elaboration of the conversion symptom, objectification of its hidden content is presented. Conclusion. The findings provide practical guidance for a psychotherapist working with conversion and psychosomatic disorders.